2014
DOI: 10.9724/kfcs.2014.30.1.011
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Garaedduk with Lentinus edodes Powder

Abstract: This research focused on investigating the effect of lentinus edodes on the Garaedduk by analyzing its quality characteristics. Through this research, it could be verified whether this improved food has the potential to develop into a functional food. 5 pieces of Garaedduk with 0, 2, 4, 6, and 8% of lentinus edodes powder were analyzed by water content, color, sensory, textural characteristics and cooking characteristics right after the production and after one day. The five Garaedduk showed significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Previous studies have recorded attempts to inhibit starch retrogradation by adding trehalose, modi ed starch [6], maltitol [7], surfactant [8] and other ingredients to garaetteok. As well, other studies have reported that the addition of rice bran [9] and germinated brown rice our [10], cactus fruit (Opuntia humifusa) powder [11], ginseng powder [12] or Lentinus edodes powder [13] to garaetteok improves the nutritional and functional quality or enhances the shelf-life of garaetteok. us far, no study has been conducted on the inclusion of potato our in garaetteok.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies have recorded attempts to inhibit starch retrogradation by adding trehalose, modi ed starch [6], maltitol [7], surfactant [8] and other ingredients to garaetteok. As well, other studies have reported that the addition of rice bran [9] and germinated brown rice our [10], cactus fruit (Opuntia humifusa) powder [11], ginseng powder [12] or Lentinus edodes powder [13] to garaetteok improves the nutritional and functional quality or enhances the shelf-life of garaetteok. us far, no study has been conducted on the inclusion of potato our in garaetteok.…”
Section: Introductionmentioning
confidence: 91%
“…Like some other rice cake types, Garaetteok are prone to microbial contamination during storage and distribution in markets and homes because of the high moisture content in these products (* 47%) (Hyun et al 2014) as well as the fact that consumers eat them without heating them. The Korea Food and Drug Administration (KFDA 2011) reported that indigenous aerobic bacteria and coliforms, respectively, were detected in Garaetteok at 4.6 and 2.1 log CFU/g in big shopping markets, at 4.7 and 1.7 log CFU/g in franchise stores, and at 3.4 and 0.7 log CFU/g in traditional markets at the time of purchase.…”
Section: Introductionmentioning
confidence: 99%